Analysis of Maximum Squat Ability in Futsal Players Who Have a History of Leg Injuries - Awaliyyah, Ulfatul Azizah; Irawan, Fajar Awang (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2024)
A person's maximum squatting ability can be known using biomechanical analysis. Biomechanical analysis is also a form of injury prevention. For futsal players, squats are one of the exercises used to determine the strength of the leg muscles. The aim of this study was to analyze the maximum squatting ability of futsal players who have a history of leg injuries. This research uses quantitative descriptive research by analyzing kinematic principles in biomechanics using kinovea 0.9.5 software. A purposive sampling technique was used in this research to determine the research sample, which consisted of 9 male athletes with a history of leg injuries. The results obtained in this study in the eccentric phase of the squat movement resulted in an average body tilt angle of 63.16 ± 9.58 degrees and a knee angle of 49.1 ± 10.61 degrees. The tilt angle of a normal person's body position during a deep squat or maximum squat position is 52.6 degrees. The knee angle during the maximum squat movement is 120-140 degrees and the squat position at full depth is 115-125 degrees. The limitation of this research is that the motion analysis was not carried out in 3 dimensions, so horizontal and frontal motion could not be analyzed.